Evaluasi Usability Sistem Reservasi Ruang Kelas dan Laboratorium Berbasis Web dengan Pendekatan System Usability Scale - Insyirah Hulul Aini; Yang Agita Rindri; M. Syafrizal Zain (LPPM STT Terpadu Nurul Fikri, 2026)
Higher education institutions play a strategic role in producing high-quality graduates and must therefore remain committed to providing adequate facilities and infrastructure for all members of the academic community. Effective facility management is crucial to ensuring the smooth delivery of educational activities, including the use of classrooms and laboratories, which are closely tied to lecture scheduling. At the State Manufacturing Polytechnic of Bangka Belitung, room management and scheduling have thus far been handled by individual departments. To keep pace with technological advancements, the campus has adopted the SEVIMA Edlink system, a platform designed to support various academic needs such as room scheduling, course scheduling, and campus announcements. However, the system has not yet fully addressed sudden schedule changes and class substitutions. This limitation creates difficulties for lecturers and students in locating replacement rooms due to the lack of real-time information on room availability. To address this issue, SIRUANGKU Polman Babel was developed as a dedicated solution. This research applies usability testing using the System Usability Scale (SUS) through questionnaires distributed to lecturers, administrative staff, and students. The results indicate a usability score of 82, classified as excellent, showing that the system performs well and is well accepted by users.